CONSIDERACIONES SOBRE LA SISTEMÁTICA DE LAS TORTUGAS DEL GÉNERO CHELUS (PLEURODIRA: CHELIDAE) y NUEVAS EVIDENCIAS FÓSILES DEL MIOCENO DE COLOMBIA Y VENEZUELA (Ameghiniana, 2014)
In light of new material from the Mioeene of Colombia and Venezuela, and based on a study of the variability in a large sample of the extant species, the features that have been used in the definition of the fossil species of Chelus are revised. The fossil species are redefined and the phylogenetic relationships are discussed. The paleobiogeographic significance of these fossil is pondered.